Recent Advances in Enantioselective C–C Bond Formation via Organocobalt Species - Yoshikai, Naohiko (Synthesis, 2019)
This Short Review describes recent developments in cobalt-catalyzed enantioselective C–C bond-forming reactions. The article focuses on reactions that most likely involve chiral organocobalt species as crucial catalytic intermediates and their mechanistic aspects.1 Introduction2 Hydrovinylation3 C–H Functionalization4 Cycloaddition and Cyclization5 Addition of Carbon Nucleophiles6 Cross-Coupling7 Conclusion
Keywords: cobalt; asymmetric catalysis; C–C bond formation; hydrovinylation; C–H functionalization; cyclization, cross-coupling